Persaingan geopolitik di Indo-Pasifik: Langkah strategis Indonesia untuk menjaga stabilitas kekuatan kawasan - Shabil, Choiru As (Maliki Interdisciplinary Journal, 2025)
The Indo-Pacific region has now assumed a strategic position as the epicenter of global geopolitics, marked by the intensifying rivalry between the United States and China. In this context, Indonesia holds a vital role, supported by its strategic geographical location, flexible foreign policy, and diplomatic capacity. This article aims to examine the strategic measures undertaken by Indonesia in response to geopolitical dynamics in the region. Using a qualitative-descriptive method based on literature studies, the discussion focuses on analyzing Indonesia’s position through traditional geopolitical theory, critical geopolitical approaches, and the concept of global interdependence. The findings reveal that Indonesia consistently upholds the principle of an independent and active foreign policy, develops the Global Maritime Fulcrum concept, and promotes multilateral cooperation through the ASEAN Outlook on the Indo-Pacific (AOIP). The conclusion of this study indicates that Indonesia seeks to position itself as a balancing actor and mediator in creating an inclusive, peaceful, and sustainable regional security order.